Evaluating social environments : a case study of residential satisfaction in elderly shared-housing settings in Cape Town, South Africa - Ndagire, Susan (Department of Construction Economics and Management, 2016)
The need for supportive non-conventional housing environments that encourage cohesion, conflict resolution, independence, self-disclosure, organisation, residential influence and physical comfort, amongst elderly residents is becoming critical, yet the evaluation of existing elderly housing settings is often overlooked. The aim of the research was to identify residents' perceptions of the social climate in shared housing settings, a non-conventional housing initiative being undertaken by non-profit organisations for the low-income elderly population group in Cape Town, South Africa. A case research study involved 45 participants living in 7 of the 13 shared houses affiliated to the Neighbourhood Old Age Homes (NOAH) organization. Using the Sheltered Care Environmental Scale (SCES), participants answered 63 'Yes / No' questions aimed at revealing their opinions of the social climate in the shared homes. The initial findings detected overall satisfaction amongst most residents regarding interfacing social dynamics, suggesting high levels of perceived independence, self-disclosure and residential influence. Mixed results were generally observed regarding interfacing social dynamics related to levels of physical comfort, organization in the homes, cohesion and conflict resolution. The findings suggest that the shared housing concept advanced by the Neighbourhood Old Age Homes (NOAH) organisation has been able to successfully promote a sense of cohesion, conflict resolution, independence, self-disclosure, organisation, residential influence and physical comfort amongst residents, thereby playing a vital role in residents' experience of residential satisfaction in these homes.